2018
DOI: 10.1111/jfbc.12635
|View full text |Cite
|
Sign up to set email alerts
|

Cereal‐derived phenolic acids and intestinal alpha glucosidase activity inhibition: Structural activity relationship

Abstract: Phenolic acids are thought to be involved in modulating the activity of intestinal α‐glucosidase which is desirable in the treatment and management of diabetes. However, limited data exist on the structural activity relationship between phenolic acid derivatives and intestinal α‐glucosidase activity inhibition. Thus five (5) hydroxycinnamic and six (6) hydroxybenzoic acid derivatives and four (4) hydroxycinnamic acid conjugates common in cereal grains were used to investigate the structural activity relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…As reported by other authors, sinapic, gallic, protocatechuic, gentistic, vanillic, and syringic acids have α-glucosidase inhibitory activity [56,57], which was also confirmed by our research. There are also many in vitro and in vivo reports on the anti-diabetic effects of gallic, protocatechuic, syringic, salicylic, ferulic, caffeic, p-coumaric, sinapic, and rosmarinic acids [29].…”
Section: Anti-diabetic Activitysupporting
confidence: 92%
“…As reported by other authors, sinapic, gallic, protocatechuic, gentistic, vanillic, and syringic acids have α-glucosidase inhibitory activity [56,57], which was also confirmed by our research. There are also many in vitro and in vivo reports on the anti-diabetic effects of gallic, protocatechuic, syringic, salicylic, ferulic, caffeic, p-coumaric, sinapic, and rosmarinic acids [29].…”
Section: Anti-diabetic Activitysupporting
confidence: 92%
“…Quercetin, and ferulic and p-coumaric acids are reported to have high α-glucosidase inhibitory activity by mixed noncompetitive inhibition (Adisakwattana et al, 2009;Li et al, 2009). The results of Mishra et al (2017) had shown that organic rye varieties have higher ferulic acid content and α-amylase inhibitory activity, while traditional rye varieties have higher catechin content and α-glucosidase The structure-activity relationship suggests that the number of hydroxyl and methoxy groups present in the aromatic ring phenolic acids decides the inhibitory activity (Malunga et al, 2018).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The enzyme inhibition potency of individual phenolic compounds through mixed, uncompetitive, and competitive type is highly correlated with their structures (Di Stefano et al., 2018; Kim et al., 2019; Malunga et al., 2018; Tadera et al., 2006). Hydroxycinnamic acids are reported to be more potent on inhibition of α‐glucosidase compared with their corresponding hydroxybenzoic acid derivatives.…”
Section: Cereal Originated Inhibitors and Inhibitor Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong positive significant correlations ( P < 0.05) were found with 4‐hydroxybenzoic acid ( r : 0.9799), vanillic acid ( r : 0.9756), p‐coumaric acid ( r : 0.9928) and ferulic acid ( r : 0.9808). It is known that cereal‐derived phenolic acids could inhibit α‐glucosidase (Malunga et al ., ).…”
Section: Resultsmentioning
confidence: 97%